Keanekaragaman Jenis dan Pemanfaatan Jamur Makroskopis di Taman Hutan Raya Bukit Mangkol Desa Teru, Provinsi Kepulauan Bangka Belitung - Julian Erika Putri; Rahmad Lingga; Henny Helmi (JURNAL BIOS LOGOS, 2024)
Macroscopic and microscopic fungi are living organisms in nature that play an important role in the balance of ecosystems and the surrounding environment. This study aimed to determine the type of macroscopic fungi and the habitat of macroscopic fungi around the Bukit Berambai Hiking trail in the Bukit Mangkol Forest Park Area, as well as to determine the use of macroscopic fungi by the people of Teru Village, Bangka Belitung Province. This research used two methods, namely qualitative and quantitative with field data collection techniques observation surveys, questionnaires, and semi-structured interviews. The research results showed that 66 taxa of macroscopic fungi consisting of two divisions, namely the Ascomycota division and the Basidiomycota division. The dominated fungi was Marasmius sp1. Most of the macroscopic fungi grew and attach to wood substrates, rotting trees, and leaf litter. The people in Teru Village used macroscopic mushrooms as food for consumption, medicine, and tradition. These mushrooms, namely Ear Mushroom (Auricularia sp), Kukur Mushroom (Schizopyllum commune), Tiung Mushroom (Hygrocybe sp 3), White Mushroom (Lentinus sajor-caju), Scale Mushroom (Phylloporus sp.), and Biring Mushroom (Gonoderma sp.).